Synthesis and Antimicrobial Activity of Novel Benzisothiazolin-3-one Acetamide Derivatives - Hu, Jun; Yu, Minjie; Yu, Peng; Xu, Yanhua (Asian Journal of Chemistry, 2014)
A series of novel 2-(3-oxobenzo[d]isothiazol-2(3H)-yl)-N-substituted phenylacetamide (4a-4e) have been synthesized from benzo [d]isothiazol-3(2H)-one (BIT) and substituted aniline. These benzisothiazolin-3-one acetamide derivatives (4a-4e) were identified by IR, 1H NMR and elemental analyses. Their antimicrobial activities were also evaluated.